Formation areas and transformation of air masses acquiring properties of dry wind in the territory of Ukraine - Сліже, Марія Олегівна; Ель Хадрі, Юссеф (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. Dry wind is a widespread dangerous phenomenon which reduces the yield of crops in Ukraine. The hot and dry winds inflict a special harm to spring grain crops. Active development of these crops falls during the spring-summer period. Dry wind can significantly reduce or completely destroy future harvests in a short time. The purpose of the article. The aim of the study is to determine the areas of initial formation of dry winds in Ukraine in recent decades and to obtain quantitative transformation value of air masses acquiring properties of dry wind on the territory of Ukraine. Methods. Daily observations at 24 meteorological stations for the period 2006-2015 were used as the initial dataset and were obtained from NOAA SATELLITE AND INFORMATION SERVICE. To determine the dry wind according to the specified criteria the data for 8 sets of daily observations of air temperature, relative humidity and wind speed were analyzed. To define the place where the formation of an air mass begins, taking dry wind properties on the territory of Ukraine, backward trajectories of the previous movement of air particles were constructed for the period of 120 hours (5 days) for the following heights: at the earth`s surface, 1500 m and 3000 m. For construction of the backward trajectories, the Air Resources Laboratory NOAA, HYSPLIT program were used. As a result of trajectories construction, temperature values, potential temperature, relative humidity of the air particle and its height above the ground, at the initial, final and intermediate points of the trajectory within 10 UTC were obtained and their transformational changes were calculated. Results. On the earth`s surface, synoptic processes of the eastern type played the main role in the formation of the dry winds. At the heights, the predominance of the western and north-western types of trajectories was noted. At the earth`s surface the main contribution to air mass temperature rise in the process of its transformation was made by the inflow of heat from the earth`s surface. At height, the reason for the increase in air temperature was the process of adiabatic descent. Dry air occurred when air masses moved through all kinds of trajectories (excluding the south-eastern form) at the surface of the earth and along the western, north-western and northern types at height. Scientific novelty and practical significance. The results of the analysis provide additional information that can be used to develop a method for forecasting dry winds on the territory of Ukraine in modern climatic conditions.